دراسة الخواص الأنزيمية لبعض العزلات الفطرية المحلية من محافظة اللاذقية في سوريا - طنجور, زنان (Latakia University Journal -Biological Sciences Series, 2018)
Isolation of fungal strains from local agricultural products is importance to produce enzymes and this explains the ability of these microorganisms to grow among containing macromolecular organic compounds. This work serves to isolate some fungal (Aspergillus niger, Geotrichum candidum, Saccharomycopsis fibuligera) and examine some enzymatic activities such as pectinase (Polygalactorunase, Pectin esterase, Indo-Polygalactorunase), Cellulase, Saccharase, β-amylase and Amyloglocosidase in liquid medium containing various carbon sources (Medium M1 Molasses 4 g%ml, M2 beet sugar residue 2%ml with wheat husks powder 3g%ml and M3 citrus sub-products 3g%ml) fermented by the selected fungal strains demonstrates that their biosynthesis potential for producing some important enzymes for use in different areas of applications, where she gave a significant production capacity of some enzymes by type of fungal and medium of culture. The studied fungus gave good results from Pectinase enzymes in three medium but high amounts by Aspergillus niger and Saccharomycopsis fibuligera has given moderate amounts of Polygalacturonase enzymes in medium M1 and M3 and very little in medium M2 and without Indogalacturonase, and that all the isolated fungal didn,t produce Cellulase in medium M1 and it gave a high activities of Cellulase in the middle M2 with Aspergillus niger and Geotrichum candidum medium, and all strains gave Invertase activity in three mediums of convergent values (40-70) activity unit and Invertase activity of A.niger in the Middle M3 override (U = 160), while Aspergillus niger and Saccharomycopsis fibuligera produce high amounts of enzymes of Amylase in three mediums. يعتبر عزل سلالات فطرية من المنتجات الثانوية الزراعية المحلية من الأهمية لإنتاج الأنزيمات وهذا يفسر مقدرة هذه الأحياء الدقيقة على النمو في أوساط تحتوي على مركبات عضوية عالية الوزن الجزيئي. يقدم هذا العمل عزل بعض الفطور الدقيقة ( Aspergillus niger، Geotrichum candidum، Saccharomycopsis fibuuligera) ودراسة بعض النشاطات الإنزيمية لهذه الفطور مثل الانزيمات البكتينية (Polygalactorunase، Pectin eterase، Indo-Polygalactorunase) والانزيمات السللوزية Cellulase و أنزيم β – فركتوفورانوزيداز Saccharase وغلوكوزيداز (amylase-β، Amyloglocosidase)، في الوسط السائل الذي يحتوي على مختلف مصادر الكربون المتخمرة (وسطM1 مولاس 4 غ% ووسط M2 تفل شوندر سكري 2% قشور قمح مطحون 3 غ % ووسط M3مخلفات حمضيات 3% ) وهذا ما يبرهن مقدرتها الكامنة على الاصطناع الحيوي لإنتاج بعض الأنزيمات الهامة من اجل استخدامها في مجالات تطبيقية مختلفة, حيث أعطت قدرات إنتاجية هامة لبعض الأنزيمات حسب نوع الفطر والوسط الزرعي. أعطت الفطريات المدروسة نتائج جيدة من الأنزيمات البكتينية في الأوساط الثلاثة لكن بكميات عالية من قبل Aspergillus niger , أما العزله Saccharomycopsis fibuligera أعطت كميات متوسطة من أنزيمات البوليغالاكتوروناز في الوسط M1 وM3 وكميات قليلة جداً في الوسط M2 وبدون اندوغالاكتوروناز، وبأن جميع السلالات المدروسة لم تنتج السيللولاز في الوسط M1 وأنها أعطت في الوسط M2 نشاطات عالية السيللولاز مع Aspergillus niger ومتوسطة Geotrichum candidum، وأن جميع السلالات أعطت نشاط إنفرتاز في الأوساط الثلاثة بقيم متقاربة (40-70) وحدة نشاط أنزيمي وان النشاط الإنفرتازي للسلالة A.niger في الوسط M3 تجاوز (U=160)، بينما السلالتين Aspergillus niger وSaccharomycopsis fibuligera تنتج كميات عالية من الأنزيمات الأميلازية في الأوساط الثلاثة.